Conceptual Effects of Audience Design in Human–Computer and Human–Human Dialogue. Issue 2 (17th February 2019) - Schmader, Christopher; Horton, William S.
ABSTRACT: Speakers in conversation often tailor referring expressions in ways that reflect beliefs about the knowledge and perspectives of specific addressees. In this study we examined whether such audience design can influence speakers' conceptualizations of referents beyond the conversation. In a Wizard-of-Oz paradigm, participants identified novel images either for an ostensible computer dialogue application or for a human partner as part of a referential communication task. Subsequently, they independently sorted the task images into discrete groups. Consistent with audience design, when interacting with the computer a greater proportion of participants' descriptions in the dialogue task focused on literal, geometric features compared with descriptions for the human partner. Importantly, participants' postdialogue sorts were also more shape-based after human–computer interaction. Different ways of attending to objects for communicative purposes can affect how speakers construe objects for themselves.